Analisis Kepuasan Pengguna Aplikasi JNF Delivery Menggunakan Metode End User Computing Satisfaction - Lisda, Lisda Kania; Nida Saripah, Siti (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
Along with technological developments, organizations/organizations are increasingly competitive, especially in the corporate service business. JNF Delivery currently comes with a new innovation, namely an application, but this application has not fully provided satisfying services to customers, because previously this service only used social media as a communication tool but since the application the customer has decreased. Therefore this study aims to analyze customer satisfaction with the JNF Delivery application using the End-User Computing Satisfaction method using 8 variables including Content, Accuracy, Format (form), Ease of Use, Timeliness (timeliness), Usability (usability), Security (security) and User Satisfaction (user satisfaction). This research was conducted by taking a sample of 28 respondents. The results of the research conducted there are variables that must be corrected, namely the Ease of Use Variable. The results of this study can be used as input for companies/organizations in improving the service quality of the JNF Delivery application, so that in the future this application can meet user needs and satisfaction.